1989
DOI: 10.2134/agronj1989.00021962008100010015x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Tall Fescue Endophyte on Plant Response to Environmental Stress

Abstract: The adverse effect of the tall fescue (Festuca arundinacea Schreb.) fungal endophyte (Acremonium coenopltialum Morgan-Jones and Gams) on animal performance is well recognized but the mutualistic effect of this fungus-grass association under environmental stress is not well understood. The objective of this study was to evaluate endophyte-free (EF) and endophyte-infected (EI) tall fescue plants from one clone for morphological and physiological responses to flooding, N rates (11, 73, and 220 mg N pot-•), and -0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
232
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(256 citation statements)
references
References 11 publications
20
232
1
3
Order By: Relevance
“…For example, in plants of F. arundinacea and other grasses, infected or not with A. coenophialum, attacks of two Coleoptera were less frequent in the first insect instars, but afterwards there were Concerning alterations due to nutrients in the soil, especially nitrogen fertilizers, there are studies showing the existence of this interaction, which is very significant. Arechavaleta et al (1989) had already verified in the F. arundinacea endophyte A. coenophialum that the production of ergopeptide alkaloids increased in soil amended with nitrogen fertilizers and during a moderate hydric stress, which consecutively altered insect-pest control.…”
Section: Genetic and Environmental Modifications Influencing Insect Cmentioning
confidence: 98%
“…For example, in plants of F. arundinacea and other grasses, infected or not with A. coenophialum, attacks of two Coleoptera were less frequent in the first insect instars, but afterwards there were Concerning alterations due to nutrients in the soil, especially nitrogen fertilizers, there are studies showing the existence of this interaction, which is very significant. Arechavaleta et al (1989) had already verified in the F. arundinacea endophyte A. coenophialum that the production of ergopeptide alkaloids increased in soil amended with nitrogen fertilizers and during a moderate hydric stress, which consecutively altered insect-pest control.…”
Section: Genetic and Environmental Modifications Influencing Insect Cmentioning
confidence: 98%
“…In tall fescue/Neotyphodium endophyte associations, several mechanisms explain the improved drought tolerance of symbiotic plants such as their enhanced root growth [5], faster leaf-rolling [1], enhanced osmotic adjustment and the maintenance of turgor levels under water stress [14]. The nitrogen deficiency tolerance of symbiotic tall fescue seems to be improved by an increased activity of glutamine synthetase regardless of nitrogen level or form favouring the utilisation of nitrogen [27].…”
Section: Introductionmentioning
confidence: 99%
“…In perennial ryegrass/Neotyphodium endophyte associations, Ravel et al [32] showed that endo- [1,11], perennial ryegrass [21 ] and meadow fescue [37]. However, the effects of endophyte on host plant growth are not consistent across host genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, en los últimos años, la festuca colonizó y dominó los bordes de caminos, favorecida por la simbiosis con un hongo endófito (Epichlöe coenofialum) que a las plantas le confiere mayor vigor, competitividad y tolerancia al estrés hídrico (Belesky and Fedders 1996). Estas características contribuirían a que festuca sea la especie dominante en las comunidades, con el riesgo de que excluya a otras especies vegetales presentes en los bordes (Arachevaleta et al 1989). …”
Section: Aplicación Del íNdice De Valor De Conservación a Un Caso De unclassified